Analyses of the Hydraulic Performance of a Continuous-Flow Drip Irrigation System Tested on a Tomato Field in Bauchi, Nigeria - Mofoke, A.L.E.; Babatunde, F. E.; Musa, S. M.; Adewumi, J. K.; Mudiare, O. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2008)
A low-cost, low-tech continuous flow drip irrigation system was constructed and tested in Bauchi. The measured hydraulic performance parameters were analysed using computer based regression, correlation and path analyses. Results showed that the total flow energy of the system is most sensitive to variations in pressure energy. Without flow regulation, fluctuation in the system discharge is influenced largely by plugging and hydraulic design parameters. However, flow regulation using ‘Medi emitter’ cushions discharge variations caused by hydraulic design. This leaves variation due to plugging as the sole source of discharge fluctuation with the system. A set of regression equations is equally provided for speedy design and evaluation of similar drip systems under same operating conditions. The set of regression equations in particular, includes a systems specific form of the Bernoulli’s Equation that may be used for computations of flow energy requirements. Inferences from the regression analysis revealed that the maximum practicable lateral length of the continuous-flow drip system is 4.6 m.